EDUsummIT: A global knowledge building community for educational researchers, practitioners, and policy makers - Lai, K.; Voogt, J.; Knezek, G.; Gibson, David (International Forum of Educational Technology & Society, 2016)
The International Summit on Information and Communication Technology (ICT) in Education (EDUsummIT) is a global knowledge building community of researchers, educational practitioners, and policy makers aiming to create and disseminate ideas and knowledge to promote the integration of ICT in education. Four EDUsummITs have been convened in The Hague, Paris, Washington, D.C., and Bangkok resulting in the development of ideas and knowledge useful and useable to ICT in education communities in integrating digital technologies into educational practices worldwide. More than two-dozen presentations by EDUsummIT participants have advocated implementation of recommendations from this knowledge building community via national and international organizations such as UNESCO, IFIP, Kennisnet, ISTE, and SITE. This paper reports findings of an evaluative study conducted at the conclusion of EDUsummIT 2015 to investigate the effectiveness and impact of EDUsummIT. Evaluative findings are proposed by the authors as useful for continuous improvement of future EDUsummITs while also serving as guiding considerations for emerging communities of practice in other fields wishing to develop and disseminate recommendations for research-based best practices at the global level.